2020
DOI: 10.1098/rsos.200636
|View full text |Cite
|
Sign up to set email alerts
|

Presence of mismatches between diagnostic PCR assays and coronavirus SARS-CoV-2 genome

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; initially named as 2019-nCoV) is responsible for the recent COVID-19 pandemic and polymerase chain reaction (PCR) is the current standard method for its diagnosis from patient samples. This study conducted a reassessment of published diagnostic PCR assays, including those recommended by the World Health Organization (WHO), through the evaluation of mismatches with publicly available viral sequences. An exhaustive evaluation of the sequence variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 77 publications
8
136
3
Order By: Relevance
“…So diagnosis of the SARS-CoV-2 might be hampered by any kind of influential changes in targeted genes ( Khailany et al, 2020 ). In our study among all the studied genomic diagnostic assay, 5 sets of genomic diagnostic assay contain the mismatches in the targeted genomic portion which is partially supported by the study of Khan and Cheung (2020) who reported mismatches in 7 sets of genomic diagnostic assay out of 27 studied assays (Supplementary Table 2) which could affect the diagnostic procedure in Bangladesh. Therefore, mutation profiles of the circulating SARS-CoV-2 isolates in the country should be taken into account.…”
Section: Discussionsupporting
confidence: 70%
“…So diagnosis of the SARS-CoV-2 might be hampered by any kind of influential changes in targeted genes ( Khailany et al, 2020 ). In our study among all the studied genomic diagnostic assay, 5 sets of genomic diagnostic assay contain the mismatches in the targeted genomic portion which is partially supported by the study of Khan and Cheung (2020) who reported mismatches in 7 sets of genomic diagnostic assay out of 27 studied assays (Supplementary Table 2) which could affect the diagnostic procedure in Bangladesh. Therefore, mutation profiles of the circulating SARS-CoV-2 isolates in the country should be taken into account.…”
Section: Discussionsupporting
confidence: 70%
“…The latter is part of the China Centers for Disease Control and Prevention (CDC) protocol with variants in 1.117% in genomes from Kerala. We have earlier reported variants in this primer site in 39.5% of the genomes from India [11] and 18.8% [56] of global genomes. This information would be potentially valuable for laboratories in selecting reagents for screening and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we estimated the genetic complexity (S Finally, we analyzed the potential impact of iSNVs and SNPs on the probes and primers used for detection of SARS-CoV-2 (15,28). To evaluate this, we downloaded the set of probes and primers sequences available at the WHO website, as well as the Arctic primers.…”
Section: Intrahost Single Nucleotide Variant (Isnv) Landscapementioning
confidence: 99%